The Binding Force of Conflict of Laws Rules on the Constitutional Judge - Sultan Mashaan, Assist. Lect. Amir; Ali Al-Janabi, Prof. Dr. Kazem (Basra studies journal, 2024)
The concept of conflict of laws in constitutional justice is a modern idea that has not been previously addressed by jurisprudence. Conflict of laws in constitutional justice is considered one of the most important guarantees for the validity of constitutional rulings. Constitutional justice is a power or constitutional body established by the state like any other authority. Its main task is fundamentally the basis for monitoring the constitutionality of laws. Therefore, constitutional litigation constitutes one of the most important means of protecting the principle of legitimacy in its general sense. The constitution reigns supreme in the legal hierarchy of every state, so it is incumbent upon the legislative authority, as the entity with the original jurisdiction to legislate laws, to consider the constraints and provisions of the highest legal document in the state. Otherwise, legislation issued may fall within the realm of unconstitutionality whenever it conflicts with the provisions of the constitution. Based on this foundation, legal rules that contradict the provisions of the rigid constitution are void, even in cases where this is not explicitly stated in the constitutional document.